ENTREPRENEURIAL EDUCATION AND SELFEMPLOYMENT ASPIRATIONS: AN EXPLORATORY STUDY OF NIGERIAN UNDERGRADUATES - Balogun, Abdulrasaq Olatunji (African Journal of Social and Behavioural Sciences, 2025)
Despite the integration of entrepreneurial programmes into university curricula, graduate unemployment rates continue to rise. This study examines the influence of entrepreneurship education on undergraduates’ aspirations for self-employment within the Faculty of Education at the University of Ilorin. Using a mixed-methods approach, the research investigates how exposure to entrepreneurship education affects students’ self-employment aspirations. The study focused on 400-level undergraduates during the 2022/2023 academic session, comprising approximately 2,733 students. A purposive sampling technique was used to select 453 final-year undergraduates, ensuring a 95% confidence level with a 0.05 margin of error. The study utilised a correlational survey design to examine relationships between variables, and stratified random sampling categorised the Faculty of Education into nine departments. A researcher-designed questionnaire and semi-structured interview were used to collect data. A retest test-retest method was used to obtain a reliability index of 0.78 for the questionnaire. Descriptive statistics was used to present the demographic characteristics of the respondents, while multiple regression was used to test the hypotheses at a 0.05 level of significance. The findings show a significant positive relationship between entrepreneurship education and self-employment aspirations, mediated by entrepreneurial self-efficacy. Qualitative insights reveal that factors such as entrepreneurial mindset, perceived feasibility, and social influences play crucial roles. The study underscores the importance of integrating experiential learning into the curriculum and designing programmes that enhance entrepreneurial self-efficacy to support students’ entrepreneurial aspirations effectively. It was recommended, among others, that universities should expand their entrepreneurial programmes to include more practical, hands-on courses. These courses should give students real-world experiences and simulate actual business challenges. Also, education programmes should aim to boost students’ confidence in their entrepreneurial skills. This can be achieved through mentorship initiatives, interactive workshops, and networking events that connect students with experienced entrepreneurs. And institutions should offer financial support options like grants or low-interest loans to help students overcome financial barriers. Additionally, providing access to resources such as incubators and co-working spaces can greatly assist student entrepreneurs.